دراسة أثر ربحية أصناف التبغ المنتجة في السّاحل السّوري على الناتج المحلّي الزراعي خلال الفترة (2000-2011). - أحمد طالب; أحمد وسيم (Latakia University Journal - Economic and Legal Sciences Series, 2016)
نظراً للأهمية الاقتصادية الكبيرة لمحصول التبغ في السّاحل السّوري، والذي يُعدّ من أهم المحاصيل الزراعية الاستراتيجية التي تساهم في رفع مستوى الحياة الاقتصادية، ركّزنا في هذا البحث على دراسة أصناف التبغ المنتجة في السّاحل السّوري من خلال دراسة الكميات المنتجة من كل صنف وتكاليف وإيرادات هذا الإنتاج والربحية الناجمة عن الإنتاج ودورها في الناتج المحلّي الزراعي خلال الفترة (2000-2011)، الأمر الذي يعطي صورة واضحة عن أثر ذلك في التنمية الاقتصادية، من خلال تطبيق الانحدار المتعدد لدراسة مدى مساهمة أصناف التبغ المختلفة والمنتجة في السّاحل السّوري في الناتج المحلّي الزراعي، وتم الاستناد إلى بيانات ومعطيات تم جمعها من المؤسسة العامة للتبغ في محافظة اللاذقية. وكان من أهم النتائج التي تم التوصل إليها: 1- حقق صنف الفيرجينيا أعلى ربحية خلال الفترة (2000-2011), في حين ادنى ربحية حققها صنف زغرين خلال نفس الفترة. 2- يعدّ صنف شك البنت يليه الفيرجينيا والتنباك من أهم أصناف التبغ المنتجة في السّاحل السّوري وأكثرها مساهمةً في الناتج المحلّي الزراعي. 3- لا يوجد تأثير لربحية أصناف البصما والبريليب والغرناطة وزغرين والبرلي في الناتج المحلّي الزراعي. Given the economic importance of tobacco in the Syrian coast, which is one of the most important agricultural crops which contribute to raising the level of economic life. In this research we focused on studying the varieties of tobacco produced in the Syrian coast by studying the quantities produced of each item and the costs and revenues of the production and profitability of production and its role in agricultural GDP during the period (2000-2011), which gives a clear picture of the impact on economic development, through applying multiple regression to examining the contribution of various tobacco varieties produced on the Syrian coast agricultural GDP, and is based on data collected from the General Organization for tobacco and cigarettes company in the governorate of Latakia. One of the most important findings: 1. Type Verginia achieved higher profitability during the period (2000-2011), while the lowest type Zegreen profit achieved during the same period. 2. - Shak Elbent followed by Verginia and Tanbak are considered the most important types and the most contributable to the Agricultural Domestic Product (ADP). 3- There is no impact of the profitability of Basma and Prilep and Gernata and Zegreen and Berly types produced in the Syrian coast on the Agricultural Domestic Product (ADP).